Chile and China, 2000–2016: The Humming Bird and the Panda - Ross-Orellana, C (Palgrave Macmillan, 2020)
The chapter deals with Chile’s foreign policy on the world stage in general, and on Asia/China in particular. Chile’s foreign policy has been primarily economic and is characterized by an approach that might be seen as somewhere between neoliberal and neorealist. As a hypothesis, Ross argues that the relations between Chile and China have taken a perspective that is historically pragmatic and superficial. Is a case of upward asymmetry that corresponds to the successful experiences Chile has had. Chile, without being a major power, is part of the global chain of value and so its natural resources are present in many industrial products. Ross concludes that China has become Chile’s main economic partner in Asia, and today is significantly more important than Japan and Korea. However, Chile lacks the political aspect in its bilateral relationship. © 2020, The Author(s).